Odvisniki v slovenščini - Žele, Andreja (Slavistična revija, 2016)
The article deals with two subgroups of subordinate clauses that have not been defined and described in Slovene grammar, i.e., content subordinate clauses within object clauses and non-participant pseudo adverbial clauses within adverbial clauses.
Keywords: podredje; skladnja; Slovene; Slovenian language; slovenščina; subordination (linguistics); syntax